Comment on “Changes in acute viral hepatitis epidemiology in the Turkish adult population: A multicenter study” - Gian Paolo Caviglia; Sharmila Fagoonee (Turkish Journal of Gastroenterology, 2019)
Cite this article as: Caviglia GP, Fagoonee S. Comment on “Changes in acute viral hepatitis epidemiology in the Turkish adult population: A multicenter study”. Turk J Gastroenterol 2018; 29: 719.